2016
DOI: 10.7567/jjap.55.04es04
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent minority carrier lifetime of crystalline silicon wafers passivated by high quality amorphous silicon oxide

Abstract: We investigated the effects of annealing on the temperature-dependent minority carrier lifetime of a crystalline silicon wafer passivated by hydrogenated amorphous silicon oxide. The annealing significantly affects the lifetime and its temperature dependence. Our device simulations clearly indicate that valence band offset significantly affects the temperature dependence. We also found a slight increase in the interface defect density after annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…It was demonstrated by the results from previous study, DE v affects t eff and temperature-dependence of t eff , according to surface recombination model [16]. The behavior of t eff for different DE v shown in Figure 5 is qualitatively in good agreement with the result of the simulation in the previous study [16].…”
Section: Fig 2 Total Bonded Hydrogen Content (C H ) and (C H Sih2supporting
confidence: 83%
See 2 more Smart Citations
“…It was demonstrated by the results from previous study, DE v affects t eff and temperature-dependence of t eff , according to surface recombination model [16]. The behavior of t eff for different DE v shown in Figure 5 is qualitatively in good agreement with the result of the simulation in the previous study [16].…”
Section: Fig 2 Total Bonded Hydrogen Content (C H ) and (C H Sih2supporting
confidence: 83%
“…It was demonstrated by the results from previous study, DE v affects t eff and temperature-dependence of t eff , according to surface recombination model [16]. The behavior of t eff for different DE v shown in Figure 5 is qualitatively in good agreement with the result of the simulation in the previous study [16]. Although the effect of DE v on the temperature-dependence of t eff is similar to the result of the previous report, the temperatures corresponding to the maximum t eff , T(t max ), are different.…”
Section: Fig 2 Total Bonded Hydrogen Content (C H ) and (C H Sih2mentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, large temperature dependence was observed from the sample with small optical bandgap, whose eff significantly decreased with increasing the measurement temperature. According to the previous report, the difference in the temperature-dependence of eff for a-SiOx:H was explained by the difference in valence band offset [7]. Therefore, it is expected that our samples also have different valence band offsets.…”
Section: Resultsmentioning
confidence: 57%
“…We have investigated i-a-Si:H deposition using FTS [4,5,6], however, its properties are not clearly understood yet. [7]. They reported that the temperature dependence of eff is strongly influenced by the properties of the passivation layer, especially by its bandgap.…”
Section: Introductionmentioning
confidence: 99%